Bustíos Romaní, C. (2010). La mujer y el niño en la historia de la salud pública peruana 1535-2002. Lima: Fondo Editorial de la Universidad Nacional Mayor de San Marcos. 243 pp. (ISBN 978-9972-2890-6-4) - Pollitt, Ernesto (2011)
No presenta resumen